Power system planning based on CSP-CHP system to integrate variable renewable energy. (1st October 2021) - Li, Xin; Wu, Xian; Gui, De; Hua, Yawen; Guo, Panfeng
Abstract: The renewable energy penetration level of power grid is forecasted by National Renewable Energy Laboratory (NREL) to reach 60% in 2050, which will bring a great challenge to accommodate the variability and uncertainty of variable renewable energy (VRE). In this paper, a hybrid CSP-CHP system is proposed to provide additional operational flexibility for power system to integrate renewable energy. First, the energy flow framework and the operational flexibility of the hybrid CSP-CHP system are analyzed. Second, a stochastic two-stage unit expansion and generation planning model based on proposed hybrid system is adopted to optimize the power system planning by considering generation technologies and policy orientation. Finally, a case study on a modified 40-bus power system is performed to research the value of hybrid CSP-CHP in 2020–2050 power system planning. Results show that the hybrid CSP-CHP plant will make up an important portion of renewable generation, and the high value of the proposed system is reflected in operational flexibility and application prospect. Highlights: A hybrid plant based on concentrating solar power and cogeneration unit is proposed. Proposing a planning model to optimize power system operation from 2020 to 2050. Extra flexibility is provided by the hybrid plant to integrate renewable energy. After 2035, building hybrid plant is beneficial due to the reduction of invest cost.